Mysidopsis gemina n. sp. (Crustacea: Mysida: Mysidae) from the northern Pacific coast of Costa Rica - Price,W. Wayne (2019)
Abstract Mysidopsis gemina n. sp. is described from protected and exposed beach habitats in the provinces of Puntarenas and Guanacaste on the northern Pacific coast of Costa Rica. Morphologically, M. gemina most closely resembles M. furca Bowman, 1957 known from the Atlantic and Gulf Coasts of North America. Both these species are unique within the genus by their distinctively sexually dimorphic telsons. The new Costa Rican species can be distinguished from M. furca and other species of Mysidopsis by a combination of having a male with biarticulated endopods on the first pleopods and pleopods 2-5 with large plate-like pseudopodia (exites). The occurrence of these characters and morphological features within the subfamily Leptomysinae is discussed.